2000
DOI: 10.1021/bc990147j
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Clearance of Poly(ethylene glycol)-Modified Immunoenzyme with Anti-PEG Monoclonal Antibody for Prodrug Cancer Therapy

Abstract: The F(ab')(2) fragment of the anti-TAG-72 antibody, B72.3, was covalently linked to Escherichia coli-derived beta-glucuronidase that was modified with methoxypoly(ethylene glycol). The conjugate (B72.3-betaG-PEG) localized to a peak concentration in LS174T xenografts within 48 h after injection, but enzyme activity persisted in plasma such that prodrug administration had to be delayed for at least 4 days to avoid systemic prodrug activation and associated toxicity. Conjugate levels in tumors decreased to 36% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 27 publications
4
51
1
Order By: Relevance
“…22,32) A similar phenomenon was observed in PEGmodified poly lactide (PLA)-nanoparticles 33) and in PEG-modified micelles. 34) Roffler and co-workers 35,36) have generated anti-PEG IgM monoclonal antibody by immunization with an antibody-PEG-modified β-glucronidase (βG) and have shown that when intravenously injected the generated anti-PEG IgM induced an accelerated clearance of PEG-modified βG from blood circulation. Our current study demonstrated that the elicited anti-PEG IgM has a cross-reactivity between PEG grafted onto proteins and PEG on nanoparticular liposome (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,32) A similar phenomenon was observed in PEGmodified poly lactide (PLA)-nanoparticles 33) and in PEG-modified micelles. 34) Roffler and co-workers 35,36) have generated anti-PEG IgM monoclonal antibody by immunization with an antibody-PEG-modified β-glucronidase (βG) and have shown that when intravenously injected the generated anti-PEG IgM induced an accelerated clearance of PEG-modified βG from blood circulation. Our current study demonstrated that the elicited anti-PEG IgM has a cross-reactivity between PEG grafted onto proteins and PEG on nanoparticular liposome (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Richter and Akerblom 27) proposed in an earlier study that the antigenic determinant of PEG may be a sequence of 6-7 -CH 2 CH 2 O-units. Roffler and co-workers 35,36) demonstrated that the monoclonal anti-PEG IgM generated by antibody-PEG-modified βG recognizes the repeating sequence (16 -CH 2 CH 2 O-units) of PEG. Thus, the anti-PEG IgM described in the present study may bind to the repeating sequence (-CH 2 CH 2 O-units) of PEG.…”
Section: Discussionmentioning
confidence: 99%
“…bG may allow both imaging and therapy of cancer with a single gene product as bG has demonstrated antitumor activity in antibody-directed enzyme prodrug therapy (ADEPT) and gene-directed enzyme prodrug therapy (GDEPT). Immunoenzymes, formed by conjugating bG to antitumor antibodies, can selectively activate glucuronide prodrugs [29][30][31][32][33][34] allow accumulation of high drug concentrations at the tumor site, 35 produce bystander killing of antigen-negative tumor cells 31 and generate long-lasting protective immunity to subsequent tumor challenge. 34 Similarly, Brusselbach et al demonstrated that cell surface display of hbG for extracellular gene-directed enzyme prodrug therapy can produce strong bystander killing and potent antitumor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Presumably the methoxyl group in the PEG chain at the terminus remote from the linker to the protein [8, WO 2004/030617 A2] was identified as a source of antigenicity, which is rather surprising since methoxyl end-capped PEGs are generally used in modern marketed PEGylated biopharmaceuticals without reports on PEG immunogenicity. However, a few reports on induction of anti-PEG immune responses in the case of repeated administration of PEGylated liposomes [30,31] or PEGglucuronidase can be found in literature [32]. High levels of PEG used as an intravenous …”
Section: Immunogenicity and Safety Of Pegylated Proteinsmentioning
confidence: 99%